Counseling on reproductive aging and oocyte cryopreservation: clinical implications for fertility preservation and reproductive outcomes (Research, Society and Development, 2026)
Reproductive aging significantly impacts female fertility due to the progressive decline in ovarian reserve and oocyte quality. Elective oocyte cryopreservation has emerged as an effective strategy for fertility preservation, particularly for women who choose to postpone childbearing. However, limited awareness of reproductive aging and available fertility preservation options remains a major challenge. This narrative review aims to analyze the clinical relevance of counseling in reproductive aging and oocyte cryopreservation, emphasizing its role in patient decision-making. Evidence suggests that effective physician–patient communication improves patient understanding, aligns expectations, and supports informed reproductive choices. Early counseling may contribute to better reproductive planning and optimize outcomes in assisted reproduction. Incorporating fertility counseling into routine clinical practice is essential to enhance patient autonomy and improve reproductive health outcomes.